1996
DOI: 10.1126/science.274.5291.1353
|View full text |Cite
|
Sign up to set email alerts
|

Chemiluminescence in the Agglomeration of Metal Clusters

Abstract: The agglomeration of copper or silver atoms in a matrix of noble gas atoms to form small clusters may be accompanied by the emission of visible light. Spectral analysis reveals the intermediate formation of electronically excited atoms and dimers as the source of the chemiluminescence. A mechanism is proposed, according to which the gain in binding energy upon cluster formation may even lead to the ejection of excited fragments as a result of unstable intermediate configurations. A similar concept was introduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
70
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(73 citation statements)
references
References 11 publications
3
70
0
Order By: Relevance
“…Before the seminal work in 2002 by Zheng and Dickson who used dendrimers as a stabilizer [12], metal NCs were only prepared in cryogenic noble gases or in solid zeolites [30][31][32]. Following this initial discovery, the Dickson group further showed that cytosine (C)-rich DNA can also stabilize fluorescent AgNCs [15], which represents the first connection between metal NCs and DNA.…”
Section: Synthesis Of Ncsmentioning
confidence: 99%
“…Before the seminal work in 2002 by Zheng and Dickson who used dendrimers as a stabilizer [12], metal NCs were only prepared in cryogenic noble gases or in solid zeolites [30][31][32]. Following this initial discovery, the Dickson group further showed that cytosine (C)-rich DNA can also stabilize fluorescent AgNCs [15], which represents the first connection between metal NCs and DNA.…”
Section: Synthesis Of Ncsmentioning
confidence: 99%
“…While such sub-nm nanoclusters are too small to have the continuous density of states (DOS) necessary to support a "plasmon" characteristic of larger free electron metal nanoparticles (1,44), the jellium model predicts that both nanoparticle plasmon widths and nanocluster transition energies of true free electron metals should scale with inverse cluster radius (40). As gas phase photodissociation experiments are unable to probe the lowest energy transitions (1), the size-dependent behavior of gold and the development of the plasmon remain poorly understood (1,7,9,(45)(46)(47).…”
Section: Absorption and Emission Of Noble Metal Clustersmentioning
confidence: 99%
“…While finding utility within electronic devices (17,18) and even as electrically excited single-photon sources at cryogenic temperatures (19), the useful properties of individual molecules have not, to date, been used to create novel optical or electroluminescent materials with behavior different from that in bulk. Recently, we reported photoactivated fluorescence from individual Ag n nanoclusters (n ϭ 2ϳ8 atoms) (20), which have been observed and calculated to absorb and emit strongly throughout the visible spectrum (21)(22)(23)(24). Here we report that these same Ag n molecules can be electrically created, thus demonstrating that it is possible to prepare room-temperature electroluminescent single molecules.…”
mentioning
confidence: 74%
“…The similarity to photoactivated single silver nanocluster fluorescence (20,28) indicates that both fluorescence and electroluminescence occur from individual Ag n molecules. Since each Ag n molecule has discrete electronic energy levels defined by its size and geometry (21)(22)(23)(24), radiative electron-hole pair recombination occurs only at the Ag nanoclusters within the discolored AgO regions of the films. This narrow recombination zone leads to extremely low film dielectricity, except at the individual electroluminescent molecules.…”
mentioning
confidence: 99%